Morocco's unique situation in the climate change arena: An analysis of climate forecasts and their link to agriculture - Ismail Ouraich; Wallace E. Tyner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Alterations in rainfall patterns and increasing temperatures due to climate change will most likely translate into yield reductions in desirable crops. In this particular context, the object of this paper is to lay down findings and results for projected yield impacts in Morocco using a well-tested crop model, CliCrop, which estimates yield impacts based on water stress. Simulation results from the CliCrop model suggest declining yields, but not by much, and variability is projected to increase marginally. These results are in sharp contrast with the other yield forecasts, which show substantial yield declines for Morocco. It is important for future research to resolve these differences.
Keywords: O13; Q54; 330; Morocco; climate change; CliCrop; agriculture; uncertainty